Reduction by coffee consumption of prostate cancer risk: Evidence from the Moli‐sani cohort and cellular models - Pounis, George; Tabolacci, Claudio; Costanzo, Simona; Cordella, Martina; Bonaccio, Marialaura; Rago, Livia; D'Arcangelo, Daniela; Filippo Di Castelnuovo, Augusto; de Gaetano, Giovanni; Donati, Maria Benedetta; Iacoviello, Licia; Facchiano, Francesco (International journal of cancer, 2017)
Meta‐analytic data on the effect of coffee in prostate cancer risk are controversial. Caffeine as a bioactive compound of coffee has not yet been studied in deep in vitro. Our study aimed at evaluating in a population cohort the effect of Italian‐style coffee consumption on prostate cancer risk and at investigating in vitro the potential antiproliferative and antimetastatic activity of caffeine on prostate cancer cell lines. 6,989 men of the Moli‐sani cohort aged ≥50 years were followed for a mean of 4.24 ± 1.35 years and 100 new prostate cancer cases were identified. The European Prospective Investigation into Cancer and Nutrition‐Food Frequency Questionnaire was used for the dietary assessment and the evaluation of Italian‐style coffee consumption. Two human prostate cancer cell lines, PC‐3 and DU145, were tested with increasing concentrations of caffeine, and their proliferative/metastatic features were evaluated. The newly diagnosed prostate cancer participants presented lower coffee consumption (60.1 ± 51.3 g/day) compared to the disease‐free population (74.0 ± 51.7 g/day) (p < 0.05). Multiadjusted analysis showed that the subjects at highest consumption (>3 cups/day) had 53% lower prostate cancer risk as compared to participants at the lowest consumption (0–2 cups/day) (p = 0.02). Both human prostate cancer cell lines treated with caffeine showed a significant reduction in their proliferative and metastatic behaviors (p < 0.05). In conclusion, reduction by Italian‐style coffee consumption of prostate cancer risk (>3 cups/day) was observed in epidemiological level. Caffeine appeared to exert both antiproliferative and antimetastatic activity on two prostate cancer cell lines, thus providing a cellular confirmation for the cohort study results. What's new? Despite the relevance for public health of the prevention of prostate cancer through lifestyle modifications, so far the epidemiological results assessing the impact of coffee consumption on the incidence of the disease are still under debate. Our study aimed at evaluating the effect of Italian‐style coffee consumption on prostate cancer risk. Reduction by Italian‐style coffee consumption (>3 cups/day) of prostate cancer risk was observed at the epidemiological level in the Moli‐sani cohort. Caffeine also appeared to exert both antiproliferative and antimetastatic activity on two prostate cancer cell lines, thus providing evidence at the cellular level supporting the cohort study results.